ANALISIS FAKTOR–FAKTOR YANG MEMPENGARUHI KEPUASAN PELANGGAN DAN IMPLIKASI PADA LOYALITAS KONSUMEN (Studi Pada Konsumen Warung Makan dan Lesehan Andheng–Andheng Tembalang) - Saragih, Jahot Rizal; Widiyanto, Ibnu (Faculty of Economics and Business Diponegoro University, 2013)
Business stalls in this era very attracted a lot of interest in businesses, so the competition was very tight. Warung Makan and Lesehan Andheng-Andheng Tembalang located at student area, sothe target market of food stalls are students. Of sales data Warung Makan and Lesehan Andheng- Andheng Tembalang april until september 2013 it is known that the number of sales still fluctuate not a gradual increase each month. The purpose of this study was to determine how much influenceof the price factor, product quality, responsiveness dish, the waiter hospitality , comfort to the level of customer satisfaction and its implications for consumer loyalty. So by knowing the factors that affect customer satisfaction and its implications for consumer loyalty is expected to be a reference for managers of Warung Makan and Lesehan Andheng-Andheng Tembalang.In conducting research independent variables are price, product quality, responsiveness dish, the waiter hospitality, comfort and the dependent variable is customer satisfaction and customer loyalty. Sample to be taken in this research was the visitors Warung Makan and Lesehan Andheng-Andheng Tembalang who've been more than two times. Due to the unknown probability sampling method in this study using non-probability sampling methods and use techniques Sampling Convenience (convenience sample). By calculation, the sample used in this study were 110 respondents to fill out the questionnaire questions or statements related to the research object.The results of this study indicate that the variable price, product quality, comfort is significantly positive effect on customer satisfaction, and customer satisfaction variable positive effect on customer loyalty. Based on the beta value of the calculation in this study was variable comfort greatest influence on customer satisfaction and its implications for consumer loyalty, it is suggested the management to increase again as the comfort of a larger space so that customer is more free and comfortable in enjoying the meal, a comfortable or free from interference from both internal and external such as buskers, beggars, etc. as well as internal factors that noise either from fellow diners as well as from the manager so that it can be, make continuous improvement to managers Warung Makan and Lesehan Andheng-Andheng Tembalang and can add interest to visit customers and to increase sales transaction of Warung Makan and Lesehan Andheng-Andheng Tembalang.